1997
DOI: 10.1080/00365521.1997.11720722
|View full text |Cite
|
Sign up to set email alerts
|

The Metabolic Importance of Unabsorbed Dietary Lipids in the Colon

Abstract: Digestion and absorption of lipids is a highly efficient process. From Western diets about 95% will be absorbed. This implies that together with lipids from endogenous sources 6-8 g of lipids will enter the colon daily. This input significantly increases during various lipid malabsorption syndromes. It has long been assumed that the biological fate of unabsorbed lipids is physiologically not relevant. However, significant microbial lipid metabolism occurs. Circumstantial evidence is arising which supports a ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 27 publications
1
17
0
Order By: Relevance
“…The daily amount of fat was 6.4 g and was added as fresh cream. This dose is in agreement with a study of Vonk et al (42), which indicated that 6-8 g of fat can enter the colon. The proteins in the culture medium were derived from different sources: Nutrilon plus™ (12.9% protein) proteose peptone (80% protein), pancreatic juice (33% protein), fresh cream (3.3% protein) and mucin (15% protein).…”
Section: Discussionsupporting
confidence: 92%
“…The daily amount of fat was 6.4 g and was added as fresh cream. This dose is in agreement with a study of Vonk et al (42), which indicated that 6-8 g of fat can enter the colon. The proteins in the culture medium were derived from different sources: Nutrilon plus™ (12.9% protein) proteose peptone (80% protein), pancreatic juice (33% protein), fresh cream (3.3% protein) and mucin (15% protein).…”
Section: Discussionsupporting
confidence: 92%
“…Finally, the selective expression of CLA-1/SR-BI in the intestinal crypts of the small intestine and in large intestine, where the absorption of lipids is quantitatively much less important, suggests that CLA-1/SR-BI should have other function(s) in addition to lipid transport or serving as a safeguard molecule for those lipids not taken up in the proximal intestine. In this regard, putative interindividual variation of CLA-1/SR-BI expression in colon could be related to the development of colon diseases caused by unabsorbed lipid metabolites (Vonk et al 1997).…”
Section: Discussionmentioning
confidence: 99%
“…The digestion and absorption of triglycerides is never complete (95-99%), implying that a mixture of glycerol, free fatty acids and undigested glycerides enters the colon (Hill, 1995;Vonk et al, 1997). The latter may be hydrolysed into free fatty acids and glycerol by bacterial lipases, which are common enzymes to a wide range of gut bacteria (Hill, 1995;Joshi & Vinay, 2007).…”
Section: Introductionmentioning
confidence: 99%